El sabor agridulce de los grupos de trabajo. - Fernández Steinko, Armando (Cuadernos de Relaciones Laborales, 2001)
This article analyses a type of organisation in the workplace known as "teamwork" or "working groups". The interest in analysing these groups lies in that, in the opinion of the author, they are a turning point, an open situation that can be implemented either with competitive instrumentalisation or democratically, based on the fundaments of solidarity. The complexity of working groups leads the author to take up issues such as the ample leeway for self-organisation and co-operation at work, allowing for participation and creativity, thereby increasing democracy within companies. By analysing working groups that actually exist, one can deduce that in their majority, these groups operative in a competitive, instrumental framework and often suffer due to a lack of resources and time, to inadequate qualifications and to limited participation. Finally, the article considers working group management in the current context of both national and international competition.